The following is written in the Adjugate Matrix Wikipedia page:


$$ p(t)~{\stackrel {\text{def}}{=}}~\det(t\mathbf {I} -\mathbf {A} )=\sum _{i=0}^{n}p_{i}t^{i}\in R[t],$$

is the characteristic polynomial of the matrix $n$-by-$n$ matrix $\mathbf A$ with coefficients in the ring $R$, then

$$ \mathrm{adj}\,(s\mathbf{I}-\mathbf{A}) = \mathrm{\Delta}\! p(s,\mathbf{A}) ~, \tag 1$$


$$ \mathrm {\Delta } \!p(s,t)~{\stackrel {\text{def}}{=}}~{\frac {p(s)-p(t)}{s-t}}=\sum _{j=0}^{n-1}\sum _{i=0}^{n-j-1}p_{i+j+1}s^{i}t^{j}\in R[s,t] $$

is the first divided difference of $p$, a symmetric polynomial of degree $n−1$.

I cannot make sense of equation $(1)$, since, for instance, $s-\mathbf A$ which would be in the denominator of $\mathrm{\Delta}\! p(s,\mathbf{A})$ is not well defined and even interpreting it as abuse of notation for $s\mathbf I-\mathbf A$ does not appear to help.

Am I just not understanding this correctly? Otherwise, is there a version of this that is actually correct?


The quotient $\frac{p(s)-p(t)}{s-t}$ has to be interpreted in the polynomial ring $R[s,t]$, where the numerator $p(s)-p(t)$ is in fact divisible by $s-t$, essentially because $$\frac{s^n -t^n}{s-t} = \sum_{i+j = n-1} s^i t^j.$$ This implies the given formula $$\Delta p(s,t) = \sum_{j=0}^{n-1} \sum_{i=0}^{n-j-1} p_{i+j+1} s^i t^j.$$ So in order to make sense of the expression $\Delta p(s,\mathbf A)$ you perform the division in $R[s,t]$ first and only then plug in the arguments $(s,\mathbf A)$, obtaining $$\Delta p(s,\mathbf A) = \sum_{j=0}^{n-1} \sum_{i=0}^{n-j-1} p_{i+j+1} s^i \mathbf A^j.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.